Melatonin Attenuates Sepsis-Induced Acute Lung Injury via Inhibiting Excessive Mitophagy - Ling J; Yu S; Xiong F; Xu T; Li S (Drug Design, Development and Therapy, 2023)
Jianmin Ling,1,2 Shanshan Yu,1,2 Feng Xiong,1,2 Tingting Xu,1,2 Shusheng Li1,2 1Department of Emergency Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430000, People’s Republic of China; 2Department of Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430000, People’s Republic of ChinaCorrespondence: Shusheng Li, Department of Emergency Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1095 Jiefang Dadao, Wuhan, 430000, People’s Republic of China, Email lishusheng@hust.edu.cnBackground: Epidemiological studies have indicated that lung injury is a frequent complication of sepsis. Mitophagy is vital to multiple pathological processes and diseases; however, its influence on sepsis-induced acute lung injury remains elusive. Melatonin has multiple antioxidant action and anti-inflammatory effects, including regulating mitophagy and inflammatory cytokine expression. Whereas, little is known about the affection of melatonin and mitophagy on CLP-induced ALI.Methods: The in vivo effect of melatonin on OPTN-mediated mitophagy was studied by CLP-induced ALI in a mouse model using C57BL/6 followed by treatment with vehicle and melatonin (30 mg/kg/d, intraperitoneal injection). ALI was assayed by lung wet /dry ratio, hematoxylin and eosin staining, and immunohistochemical staining. Signaling pathway changes were subsequently determined by Western blotting and immunofluorescence staining. The effects of melatonin on STAT3 activation and TNF-α production were detected by Western blotting, PCR, and immunohistochemical staining.Results: Our results indicated that OPTN, mitophagy adaptors were significantly repressed in CLP-induced ALI, accompanied by overactivation of mitophagy and inflammation. At the same time, we found that melatonin treatment alleviated ALI caused by CLP, and the effect was highly correlated with OPTN-related mitophagy. Furthermore, we demonstrated that OPTN-related mitophagy, which was normalized by melatonin, blocked STAT3 involved epithelial barrier and inflammation in vivo.Conclusion: Overall, our results confirm that mitophagy is adjusted by melatonin in the CLP-induced ALI. Moreover, manipulation of mitophagy through melatonin could be a possible treatment to reduce sepsis-associated lung injury.Keywords: melatonin, sepsis, acute lung injury, mitophagy, inflammation